The influence of genotype, sex, and dietary lysine on subprimal cut distribution of 230 and 280 lb. finishing pigs - Dunn, B.L.; Friesen, K.G.; Nelssen, Jim L.; Goodband, Robert D.; Tokach, Michael D.; Unruh, John A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred sixteen pigs were used to determine effects of the interrelationship among genotype, sex, and dietary lysine on subprimal cut distribution of pigs fed to 230 and 280 lb. In a 2 X 2 X 2 factorial arrangement, barrows and gilts, previously characterized as having either high or medium lean-gain potential, were fed one of two dietary lysine regimens. One pig per pen was slaughtered when the mean weight of pigs in a pen reached 230 lb and the remaining two pigs were fed until the mean weight reached 280 lb. When fed to either 230 or 280 lb, carcasses from high-lean genotype pigs or gilts had higher percentages of combined closely trimmed boneless ham, loin, and shoulder than medium-lean genotype or barrow carcasses, respectively. Dietary lysine level had minimal influences on subprimal cut distribution. The highest percentages of major lean subprimal cuts for pigs fed either to 230 or 280 lb were in highlean genotype gilts.
Keywords: Swine; Pork; Lysine; Sex; Genotypes; Meat yield